Pitfalls of Participatory Programs: Evidence from a Randomized Evaluation in Education in India - Banerjee, Abhijit V. (2012)
Participation of beneficiaries in the monitoring of public services is increasingly seen as a key to improving their quality. We conducted a randomized evaluation of three interventions to encourage beneficiaries' participation to India: providing information on existing institutions, training community members in a testing tool for children, and training volunteers to hold remedial reading camps. These interventions had no impact on community involvement, teacher effort, or learning outcomes inside the school. However, in the third intervention, youth volunteered to teach camps, and children who attended substantially improved their reading skills. This suggests that citizens face constraints in influencing public services.